Combining salicylic acid and trisodium phosphate alleviates chilling injury in bell pepper (Capsicum annuum L.) through enhancing fatty-acid desaturation efficiency and water retention. (15th October 2020) - Ge, Wanying; Zhao, Yingbo; Kong, Ximan; Sun, Huajun; Luo, Manli; Yao, Miaomiao; Wei, Baodong; Ji, Shujuan
Highlights: Trisodium phosphate (TSP), salicylic acid (SA) and TSP + SA treatments delayed and alleviated CI symptoms of bell pepper. TSP, SA, TSP + SA treatments suppressed LOX activity and MDA content, enhanced GSH and AsA content. Combined TSP + SA treatment was more effective than individual. Greater cold tolerance is apparently linked to moisture retention and elevated fatty-acid desaturation. TSP + SA treatment prevented membrane degrading and cytoplasm leakage. Abstract: Chilling injury (CI) restricts the quality and shelf life of bell pepper fruits; reducing these CI-induced detrimental effects is therefore of high economic and agricultural relevance. Here, we investigated the effects of trisodium phosphate (TSP), salicylic acid (SA), and TSP + SA treatments on pepper fruits under cold stress at 4 °C for 25 d. Combined TSP + SA treatment performed an optimal effect. Specifically, TSP + SA treatment enhanced fatty-acid desaturation efficiency, as indicated by the increased expression of key fatty acid desaturase genes, and higher content of unsaturated fatty acids. Meanwhile, TSP + SA treatment inhibited the CI-induced membrane damage, manifested as lower electrolyte leakage and malondialdehyde content. Furthermore, low field-nuclear magnetic resonance and proline content also revealed that TSP + SA treatment mitigated CI through enhancing water retention in pepper fruits. Collectively, our results may shed new light on optimizing the low-temperature storage conditions of post-harvest peppers.